Effects of Listening to Al Kauthar Verse on Brain Physiology - Norsiah, Fauzan; Norazila, Abd Aziz (Universiti Sains Islam Malaysia 2015, 2018)
This paper investigates the outcomes of a preliminary research brainwaves reaction when listening to Al-Khauthar. Quantitative electroencephalogram machine (EEG) was used to observe and record the brainwave activities while listening to Al- Khauthar. Findings shows that the dominant brainwave during listening to Al- Khauthar is Delta with 27.97 MV . In addition, the findings obtained from the data collected; it show that all brain regions which are Prefrontal, Frontal,Occipital, Post-central, Parietal and Temporal lobe are involved. Delta waves helped to stimulate the growth hormone and repair the brain cells or tissues. To conclude, listening to Al- Khauthar brought about calmness and relaxation to body and mind. Listening to the verse might stimulates the production of growth hormone and melatonin that control our sleep and wake up activites and consequently our relaxation.